2006
DOI: 10.1007/s11325-005-0049-3
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate regularity analysis obtained from pulse oximetric recordings in the diagnosis of obstructive sleep apnea

Abstract: Approximate entropy (ApEn) is a technique that can be used to quantify the irregularity or variability of time series. We prospectively evaluated the validity of ApEn of heart rate data obtained from pulse oximetric recordings as a diagnostic test for obstructive sleep apnea (OSA) in patients clinically suspected of suffering this disease. A sample of 187 referred outpatients (147 men and 40 women), with a mean age of 57.9+/-12.8 years and a body mass index of 29.5+/-5.5 kg/m(2), clinically suspected of having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
1
6
0
5
Order By: Relevance
“…Based on their founding, head-up tilt resulted in a significant reduction in sample entropy of R-R intervals and cross-sample entropy, while mental arithmetic stress resulted in a significant reduction in coupling directed from R-R to QT. See also282930.…”
mentioning
confidence: 99%
“…Based on their founding, head-up tilt resulted in a significant reduction in sample entropy of R-R intervals and cross-sample entropy, while mental arithmetic stress resulted in a significant reduction in coupling directed from R-R to QT. See also282930.…”
mentioning
confidence: 99%
“…Similarly, the entropy of respiratory sounds has been found to be higher in non-healthy subjects [ 36 ] and the entropy of mechanomyogram signals is also higher as the severity of COPD increases [ 52 ]. In the presence of OSAS, different studies reported higher non-linear measures values of overnight oximetry [ 33 , 34 ], airflow [ 35 ], and heart rate [ 21 , 26 , 53 ] derived from whole-night PSG. In these studies, it has been found that direct presence of apnoeic events modifies the normal cardiorespiratory dynamics towards higher disorderliness or disorganization, i.e., higher entropy.…”
Section: Discussionmentioning
confidence: 99%
“…It reflects changes with periodicities between 30 s and 70 s (0.014–0.033 Hz). The power spectrum in this frequency band has been found to be related to the repetition of apnoeic events during the night [ 26 , 28 ]. It is usually normalised to the total signal power (OSASFn).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ACAT algorithm also showed a good performance [AUC, 0.979 (95 % CI, 0.912–0.998); 90 % sensitivity and 100 % specificity] for this database [19]. Although only a few studies have examined the performance of the algorithms in clinical settings, they have reported modest diagnostic accuracies [18, 20, 29]. In a study of 150 patients referred to a university hospital for clinically suspected SDB, Roche et al [18] reported that an algorithm that used the relative power of the very low frequency component detected patients with AHI ≥15 with an AUC of 0.70, a sensitivity of 64 %, and a specificity of 69 %.…”
Section: Discussionmentioning
confidence: 99%